2015
DOI: 10.1163/15707563-00002479
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relatedness provides support for a species complex of myxosporeans infecting the Indian major carp, Labeo rohita

Abstract: Myxozoans are an economically important group of microscopic metazoan parasites of fish. The myxozoan species Thelohanellus filli infects commercially important freshwater fish both in wild and in cultured habitat. This parasite causes gill hemorrhagic disease and significant damage to the respiratory surface of the infected fish. In the present study, the 18S rDNA gene sequence of morphologically identified T. filli infecting the gill lamellae of the Indian major carp, Labeo rohita, was characterized. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…A large number of myxozoan species have been described infecting freshwater fishes in wetlands and aquaculture in Punjab (Singh and Kaur 2012a, b, c, d;Singh and Kaur 2014;Kaur 2014;Kaur et al 2014a, b;Kaur and Katoch 2014: Kaur and Gupta 2015Dar et al 2017). In the present study, two new species belonging to the genus Myxobolus Butschli infecting gill lamellae and gill filaments of Cirrhinus mrigala (Ham.)…”
Section: Introductionmentioning
confidence: 57%
“…A large number of myxozoan species have been described infecting freshwater fishes in wetlands and aquaculture in Punjab (Singh and Kaur 2012a, b, c, d;Singh and Kaur 2014;Kaur 2014;Kaur et al 2014a, b;Kaur and Katoch 2014: Kaur and Gupta 2015Dar et al 2017). In the present study, two new species belonging to the genus Myxobolus Butschli infecting gill lamellae and gill filaments of Cirrhinus mrigala (Ham.)…”
Section: Introductionmentioning
confidence: 57%
“…is challenging, as many species are morphologically similar (Chen and Ma, 1998). Efforts have been made to address this issue by supplementing morphological descriptions with 18S rDNA sequence data (Kent et al, 2001) In North India, many species of myxozoan parasites were reported in freshwater fishes from wetlands in Punjab (Kaur and Singh, 2009, 2011d, 2012aSingh and Kaur, 2015;Kaur et al, 2014aKaur et al, , 2016Kaur and Gupta, 2015;Gupta and Kaur, 2016). The present study describes the morphological and molecular aspects of a new species, M. puntiusii, found parasitizing the caudal fin of Puntius sophore (Ham.)…”
Section: Introductionmentioning
confidence: 88%
“…According to Andree et al (1999), PCR was done at the final volume of 25 µl using the primers that amplified the fragments of approx. 1121 bp of the 18S protocol (Kaur & Gupta, 2015). Thereafter, PCR products were electrophoresed on 2% agarose gel in 0.5 mg/ml ethidium bromide in 1X Trisacetate-EDTA (TAE) buffer, and the size was estimated by comparison with 100 bp Invitrogen DNA Ladder.…”
Section: Molecular Analysismentioning
confidence: 99%